2019
DOI: 10.3389/fonc.2019.00666
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance to CDK4/6 Inhibitors: Potential Implications and Biomarkers for Clinical Practice

Abstract: The recent arrival of CDK4/6 inhibitor agents, with an approximate doubling of progression-free survival (PFS) associated with their use in hormone receptor-positive, HER2-negative advanced breast cancer (BC), has radically changed the approach to managing this disease. However, resistance to CDK4/6 inhibitors is considered a near-inevitability in most patients. Mechanisms of resistance to these agents are multifactorial, and research in this field is still evolving. Biomarkers with the ability to identify ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 80 publications
3
115
0
2
Order By: Relevance
“…Although initially beneficial, resistance to CDK4/6 inhibition arises in almost all patients within two years thus limiting durable responses. Currently, there are no biomarkers that can predict treatment response or early resistance [26]. Here, we identified a number of clinically relevant pathways that are associated with resistance to palbociclib, largely focusing on metabolic alterations and oncogenic signaling such as nucleotide metabolism, inositol metabolism, cell cycle, immune regulation and DDR.…”
Section: Discussionmentioning
confidence: 99%
“…Although initially beneficial, resistance to CDK4/6 inhibition arises in almost all patients within two years thus limiting durable responses. Currently, there are no biomarkers that can predict treatment response or early resistance [26]. Here, we identified a number of clinically relevant pathways that are associated with resistance to palbociclib, largely focusing on metabolic alterations and oncogenic signaling such as nucleotide metabolism, inositol metabolism, cell cycle, immune regulation and DDR.…”
Section: Discussionmentioning
confidence: 99%
“…CDK4/6 inhibitors were approved by the FDA for the treatment of Hormone Receptor (HR)-positive and Human Epidermal Growth Factor Receptor 2 (HER2)-negative breast cancer. However, most patients inevitably develop resistance for multifactorial reasons [30,31]. Recently, our group demonstrated that the JAK-STAT pathway plays a role in acquired resistance of CDK4/6 inhibitors in bladder cancer [32].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used previously and generated clinically relevant results, identifying cyclin E1 overexpression and Rb loss as genetic traits of palbociclib resistance [13,29,30]. Importantly, mammalian target of rapamycin complex 1 (mTORC1) activation is also reported to play an important role in the resistance mechanism and, currently, PI3K inhibitors (i.e., blocking PI3K/mTOR pathway) are in clinical trials in combination with CDK4/6 inhibitors [31]. Importantly, mTOR activation has also been reported to enhance glycolytic traits of the resistant cells, suggesting that glycolytic function may be under PI3K/mTOR signaling control in cancer and other pathologies [17].…”
Section: Discussionmentioning
confidence: 99%